The effects of religiosity in ads toward brand image - Mohd Fauzi Harun; Fareez Vincent Amos@Mohd Fadly; Nik Narimah Nik Abdullah; Nur Safinas Albakry (Penerbit Universiti Kebangsaan Malaysia, 2023)
Religious beliefs play a significant role including brand preference by adapting symbolic associations to motivate better engagement, which reflects the audience's personal behavioral dimension (values and beliefs) in marketing activities. However, religiosity's role in the development of a brand image by religious visual communication design is rarely discussed, even though there are emotional connections in the marketing activities. This study’s objective is to understand how culture, specifically religiosity, could affect the brand image through local ads’ appeal. Five different brands from outdoor advertisements were selected as a case study for this research. A qualitative study was employed to obtain an in-depth appreciation in sociological context. Thus, seven informants of expertise participated using semi-structured interviews as the data collection tool and continued with thematic analysis assisted by Atlas.ti in identifying patterns across the collected datasets. Three main themes were discovered which are; commodification, halalness and trustworthiness. Religiosity is said to be positively affected by religious visual communication design in ads. These emotional strategies in marketing easily gain attention from their values, which are later translated into trustworthiness which is called commodification. Religious cues in ads are easily associated as the products’ brand image even though some are considered as misled. A fine line between marketing and religion needs to be drawn by the marketers or advertisers to avoid exaggeration and becoming a norm in marketing.